ARTS‐BASED EDUCATIONAL RESEARCH DISSERTATIONS: REVIEWING THE PRACTICES OF NEW SCHOLARS - Sinner, Anita; Leggo, Carl; Irwin, Rita; Gouzouasis, Peter; Gouzouasis, Peter; Grauer, Kit (Canadian Journal of Education/Revue canadienne de l'éducation, 2006)
With this review, we explore the practices of arts‐based educational research as documented in dissertations created and written over one decade in the Faculty of Education, University of British Columbia. We compile and describe more than thirty dissertations across methodologies and methods of inquiry, and identifiy three pillars of arts‐based practice – literary, visual, and performative. In this review, we trace the beginnings of a new stream of practice that is interwoven in some of these dissertations and underpins many of them: the methodology of a/r/tography. Four attributes underpin this collection of dissertations: a commitment to aesthetic and educational practices, inquiry‐laden processes, searching for meaning, and interpreting for understanding. Les auteurs explorent les pratiques ciblées et analysées dans les recherches en éducation axées sur les arts, notamment dans les thèses réalisées au cours d’une décennie à la Faculté des sciences d’éducation de l’University of British Columbia. Ils ont compilé et décrit plus d’une trentaine de travaux faisant appel à diverses méthodologies et protocoles de recherche et identifié trois grands axes en matière de pratiques axées sur les arts – littéraire, visuel et de performance Dans ce tour d’horizon, les auteurs retracent les débuts d’une nouvelle approche qui apparaît dans certains des travaux et qui sert même de fondement à un grand nombre d’entre eux : la méthodologie de l’a/r/tographie. Cet ensemble de travaux présente quatre caractéristiques communes : une importance accordée aux pratiques esthétiques et pédagogiques, des processus axés sur la recherche, une quête de sens et un souci d’interprétation en vue de comprendre.